Unknown geometrical constraints estimation and trajectory planning for robotic door-opening task with visual teleoperation assists. Issue 3 (5th June 2019) - Xing, Hongjun; Xia, Kerui; Ding, Liang; Gao, Haibo; Liu, Guangjun; Deng, Zongquan
Abstract : Purpose: The purpose of this paper is to enable autonomous door-opening with unknown geometrical constraints. Door-opening is a common action needed for mobile manipulators to perform rescue operation. However, it remains difficult for them to handle it in real rescue environments. The major difficulties of rescue manipulation involve contradiction between unknown geometrical constraints and limited sensors because of extreme physical constraints. Design/methodology/approach: A method for estimating the unknown door geometrical parameters using coordinate transformation of the end-effector with visual teleoperation assists is proposed. A trajectory planning algorithm is developed using geometrical parameters from the proposed method. Findings: The relevant experiments are also conducted using a manipulator suited to extreme physical constraints to open a real door with a locked latch and unknown geometrical parameters, which demonstrates the validity and efficiency of the proposed approach. Originality/value: This is a novel method for estimating the unknown door geometrical parameters with coordinate transformation of the end-effector through visual teleoperation assists.